The endocannabinoid anandamide prevents TH17 programming of activated T lymphocytes while preserving TH1 responses - Kiprina, Anastasiia; Teichmann, Tom; Martín Giménez, Virna Margarita; Xu, Wenqing; Sailer, Fiona; Windbergs, Maike; Manucha, Walter; Weigert, Andreas; Brandes, Ralf P. (Frontiers in Pharmacology, 2024)
IntroductionAnandamide (AEA) is an endocannabinoid that has recently been recognized as a regulator of various inflammatory diseases as well as cancer. While AEA was thought to predominantly engage cannabinoid (CB) receptors, recent findings suggest that, given its protective anti-inflammatory role in pathological conditions, anandamide may engage not only CB receptors.MethodsIn this study, we studied the role of exogenous AEA in a mouse AirPouch model of acute inflammation by examining immune cell infiltrates by flow cytometry. Human primary immune cells were used to validate findings towards immune cell activation and migration by flow cytometry and bead-based ELISA.ResultsWe found that AEA decreases the acute infiltration of myeloid cells including granulocytes and monocytes into the inflamed area, but unexpectedly increases the number of T cells at the site of inflammation. This was related to AEA signaling through nuclear receptor subfamily 4A (NR4A) transcription factors rather than CB receptors. Exploring regulatory mechanisms in the human system, we found that AEA broadly inhibits the migratory capacity of immune cells, arguing for blocked emigration of T cells from the inflamed tissue. Taking a closer look at the impact of AEA on T cells revealed that AEA profoundly alters the activation and exhaustion status of CD4+ T and CD8+ T cells, thereby strongly inhibiting TH17 responses, while not altering TH1 differentiation.DiscussionThese data suggest that AEA has the potential to block chronic inflammation without influencing crucial anti-viral and anti-microbial immune defense mechanisms, and may therefore be an attractive molecule to interfere with the establishment of chronic inflammation.